2002
DOI: 10.1007/s10350-004-6181-5
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Incontinence Severity Index After Fistulotomy

Abstract: The Fecal Incontinence Severity Index is an excellent tool to gauge quality of life after fistulotomy. Fecal Incontinence Severity Index scores >30 predict a detrimental effect on quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 7 publications
3
61
0
6
Order By: Relevance
“…The median number of patients contributed by each participating surgeon was 8 (mean, 9.8; range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and median number of patients contributed by practice was 14 (mean, 20.4; range, 1-62). The median patient age was 46 years (mean, 61.7; range, 18 -85 years), including 162 males and 83 females.…”
Section: Resultsmentioning
confidence: 99%
“…The median number of patients contributed by each participating surgeon was 8 (mean, 9.8; range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and median number of patients contributed by practice was 14 (mean, 20.4; range, 1-62). The median patient age was 46 years (mean, 61.7; range, 18 -85 years), including 162 males and 83 females.…”
Section: Resultsmentioning
confidence: 99%
“…It has therefore been argued that different questions need to be asked in anal disease, 21 Faecal incontinence is known to have a detrimental impact on QOL, 22 and it has been suggested that QOL following fistula surgery strongly correlates with reduced faecal continence. 19,23,24 QOL with recurrent disease needs to be balanced against the QOL associated with reduced continence. The Fecal Incontinence Severity Index (FISI) was devised, 25 validated, 23 and then used to predict QOL following fistula surgery, 24 which indicated that QOL is strongly correlated with FISI scores.…”
Section: Discussionmentioning
confidence: 99%
“…19,23,24 QOL with recurrent disease needs to be balanced against the QOL associated with reduced continence. The Fecal Incontinence Severity Index (FISI) was devised, 25 validated, 23 and then used to predict QOL following fistula surgery, 24 which indicated that QOL is strongly correlated with FISI scores. In our study, no overall correlation was found between continence score and QOL; however, urgency was found to have a significant impact on QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Various techniques have been described including fistulotomy [1][2][3][4], fistulectomy [5] and advancement flap procedures [6][7][8][9][10][11]. The results of fibrin glue treatment have been disappointing and the technique has largely been abandoned [12].…”
Section: Introductionmentioning
confidence: 99%